Political economy of nationalism - Seers, Dudley (New York, 1983)
It is time to abandon the idea that the interests of all nations are compatible. Resource limitations mean inevitable conflicts of interest. This book challenges the orthodoxies of 'development economics' and aid policies. It argues that both Marxism and conventional 'Western' economics underestimate nationalism as a strong and necessary protection against the USA or USSR. Yet this does not imply that a government can opt out from either of the two neo-colonial systems. What a country can do depends on its size, location, and resources, and on the ethnic basis for nationalism. Much also depends on the skill and determination of the political leadership. Because of the importance of size for economic and military purposes, regional blocs, such as the European Community, are more viable than nations. The possibility of an 'extended nationalism' to cover all Europeans-or all Latin Americans, etc. - is explored. This book should appeal to anyone who is interested in development and especially those who wish to be challenged by an unconventional approach.
Keywords: Nationalism -Economic aspects